(untitled) (Journal of Medicine, 2022)
Objective: Coronavirus pandemic has spread globally. It has affected people mentally and economically.These types of pandemics often lead to post-traumatic stress traumatic syndrome among people. Researchdata is needed to know the PTSD due to the coronavirus pandemic among the general population. Materials and Methods: This study is cross-sectional. Data was collected in 3 days from the generalpopulation of Karachi through an online questionnaire regarding age, gender, education, profession,precautionary measures, awareness related to COVID, satisfaction related to COVID, Health informationawareness. IESR scale was used to assess post-traumatic stress syndrome. A total of 241 respondentswere involved. Results: Moreover, 11.2% had partial PTSD, 4.1% had PTSD and 34.9% had PTSD high enough to suppressthe immune system. Among the respondents majority belong to age group 20 to 30, female, student,undergraduate, were aware of COVID, tested positive for COVID, knew someone tested positive forCOVID, applied precautionary measures, avoided going out, worried about your family members gettingCOVID, satisfied with health information available and were aware of health information available. Agegroup 20 to 30, Male gender, matric education level, housewives, tested positive for COVID, applyingprecautionary measures, applying social distancing, having present physical symptoms, worrying aboutyour family members getting COVID, was associated with high IESR score and PTSD (p<0.05). Awarenessrelated to COVID-19 and avoiding going out was associated with low IESR scores and were protectivefactors related to PTSD(p<0.05). Tested positive for COVID, presence of past physical symptoms, satisfactionwith health information available, and awareness of health information available were not significantlyassociated with IESR score and PTSD (P>0.05) Conclusion: During the outbreak of the coronavirus pandemic more than half of the respondentsreported partial to severe PTSD. Age group 20 to 30, Male gender, matric education level, housewives,tested positive for COVID, applying precautionary measures, applying social distancing, having presentphysical symptoms of COVID, worrying about your family members getting COVID are the vulnerablegroups which need urgent attention related to PTSD. Awareness related to COVID-19 and avoiding goingout are protective factors related to PTSD hence these factors can be considered by higher authoritiesto make psychological policies. J MEDICINE 2022; 23: 36-41